Normal Map Estimation in the Wild - Condor Lacambra, Jorge; Lagunas Arto, Manuel; Delanoy, Johanna; Masiá Corcoy, Belén; Gutiérrez Pérez, Diego (Jornada de Jóvenes Investigadores del I3A, 2021)
We propose a method to estimate normal maps of objects in the wild, from just a single RGB image. Our approach is based on deep learning, and we use synthetic data to train our network. Lastly, we show its applicability by improving the results of image-based appearance editing tasks.